A Cohort Study to Assess Cognitive Impairment and Its Effects on Older Patients in the Orthopedic Rehabilitation. (18th February 2022) - Zhang, Han; Pang, Bo; Ma, Zheng; Dong, Huimei; He, Hongyi; Jiang, Lan
Abstract : Background . The cognitive role of older patients is regularly not investigated in orthopedic rehabilitation, after the elective as well as the nonelective operation. The objective of this research is to investigate the cognitive disorder and its influence over the duration of stay along with the functional consequences of the older patients who were admitted to orthopedic rehabilitation. Material and Methods . The inclusion criteria for this study were the patients with age above 50 years; who were admitted with the detection of orthopedic impairment and the surgery both elective and nonelective, investigated utilizing the MoCA (Montreal Cognitive Assessment) over admission, MBI (Modified Barthel Index), and FIM (Function Independent Measure) over admission and discharge status; and were discharged from the hospital. The demography, as well as the clinical data, comprising of the duration of stay, age and the detection was also reported. Result . Of the 109 admitted patients, 80 patients were included in the study where n = 47 (58.75%) patients were females and n = 33 (41.25%) were males. The age group range was 50 to 94 years with a mean age of 78.5 years (SD = 8.27). The diagnostic groups included for the study were fractured neck of femur ( n = 34; 42.5%), orthopedic surgery ( n = 22; 27.5%), and other orthopedic surgery ( n = 24; 30%). The mean duration of rehabilitation stay was reported as 34 (4.39), where the MoCA was reported as 22.17 (2.44); functional independence measures were as follows: motor admission as 53.97 (7.55), motor discharge as 76.27 (5.35), cognitive admission as 30.71 (1.99), and cognitive discharge as 31.85 (1.94). Here, the diagnosis was done over the fractured neck of the femur (i.e., NOF being 34 (42.5%), elective surgeries 22 (27.5%), and other orthopedic as 24 (30%)). Conclusion . An excessive percentage of older-age patients in a rehabilitation unit with elective as well as nonelective diagnoses comprises the cognitive disorder. The cognitive screening was advised for all the older age patients in the rehabilitation units to report a specific rehabilitation plan to enhance the consequences along with the duration of stay. There is further study required to explore different cognitive strategies to enhance the rehabilitation consequences among older-age orthopedic patients.